Kepemimpinan Transformasional Pendidikan Di Era Society 5.0 - Mira Marisa; Saipul An Nur (SOSIOEDUKASI, 2021)
This article examines how transformational leadership of education in the era of society 5.0. As is known before the introducedness of the era has arisen the industrial revolution 4.0. Therefore, it is a challenge and also an opportunity for education leaders to be able to change the mindset of education leaders to be able to manage transformational leadership, just as this in the education sector the principal is the leader. Therefore, the data collection method in this article uses library research with data collection using literature studies studied from various sources such as journals, books, and so on. Thus, what emerges from this article is how the efforts of an education leader respond to the transformational existence of education in the era of society 5.0. Keywords: Leadership, Education Transformation, Society 5.0